The Pronunciation of the Regular Past Tense of English Verbs in Junior High School Students - Humaira Restu Maulidia (Ma'soem University, 2020)
This research aims at describing how the pronunciation of regular past tense of English verb should be and the variation of the regular past tense of English verb. Qualitative design is chosen in this study. The data gathered and analyzed through the main theories in the theoretical background. The data analyzed showed that in the first paragraph, there are 7 of regular past tense of English verb; lived, named, asked, granted, touched, amazed and turned. In the second paragraph, there are 10 of regular past tense of English verb; changed, cried, loved, touched, shocked, beloved, turned, begged, granted, and realized. Each of words is classified based on the environment. So that, it can be concluded that there are 7 words after voiced segments; lived, named, turned, loved, beloved, begged, and cried. In voiceless segments, there are 7 words of regular past tense of English verb; asked, shocked, amazed, changed, touched, and realized. Furthermore, there is non-nasal alveolar stop; granted. Those words pronounced variously by the students.